Prospects of cognitive-motor entrainment: an interdisciplinary review - Schmid, Daphne G. (Frontiers in Cognition, 2024)
Entrainment theory, a multidisciplinary concept referring to the automatic synchronization of oscillatory patterns, can be used to explain interactions across motor production, cognition, and environmental processing. This review summarizes findings from the three primary categories of naturally occurring neural entrainment: body-brain entrainment of involuntary self-produced rhythms, bottom-up entrainment between environmental stimuli and the brain, and top-down neural entrainment of self-produced processes. Studies evaluating entrainment’s impact on cognition suggest that synchronized neural activation may alleviate cognitive constraints. Entrainment has also been therapeutically implemented to decrease motor production variation and enhance movement quality. When considering the evidence for entrainment's ability to decrease the attentional load of a task and increase cognitive or motor production quality, the oscillatory synchronization of a cognitive and motor task may be a promising technique that can be applied to dual-tasking. An emerging body of literature suggests that cognitive-motor entrainment may alleviate dual-task cost and, in some cases, lead to a higher quality of psychological and physiological task performance than when the same tasks are performed in isolation. We propose pathways for future research and emphasize the therapeutic relevance further experimentation on the topic of entrainment may provide. By understanding how to maximize neural entrainment's cognitive and motor benefits, scientists and practitioners may be able to harness its benefits to enhance learning and rehabilitative practices.